KEBINASAAN TUBUH DAN KESELAMATAN ROH EKSEGESIS1 KORINTUS 5:1-5 - Helwen Pattikawa (Jurnal Dinamika Pendidikan, 2019)
ABSTRACT This study aims to, first, explain the problem that is the basis of sin in the Corinthian church with regard to 1 Corinthians 5: 1-5; second, explain and describe the relationship between the destruction of the body of the person surrendered to the devil and the salvation of the Spirit. Text 1 Corinthians 5: 1-5 discusses the sin of adultery or fornication that occurs in the Corinthian church, and the attitude of the church that let even joy with the sin. Paul very firmly rebuked the Corinthians for their attitude, even Paul advised that people who commit sexual immorality must be destroyed by submitting their bodies to the devil so that they have or obtain the salvation of the Spirit, or in other words so that the person's Spirit is saved, his body must be surrendered to the devil. Keywords: estruction of the body, salvation of the spirit, fornication, morals. ABSTRAK Penelitian ini bertujuan untuk,pertama, Menjelaskan masalah yang menjadi dasar dari dosa dalam jemaat Korintus berkaitan dengan 1 Korintus 5:1-5; kedua, Menjelaskan dan menguraikan hubungan antara kebinasaan tubuh orang yang diserahkan kepada iblis dengan keselamatan Roh.Teks 1 Korintus 5:1-5membahastentang dosa perzinahan atau percabulan yang terjadi di dalam jemaat Korintus, dan sikap jemaat yang membiarkan bahkan bersuka cita dengan dosa tersebut. Paulus dengan sangat tegas menegur jemaat Korintus atas sikap mereka, bahkan Paulus menasehati supaya orang yang melakukan percabulan harus dibinasakan tubuhnya dengan cara diserahkan kepada iblis sehingga memiliki atau memperoleh keselamatan Roh, atau dengan kata lain supaya Roh orang itu diselamatkan maka tubuhnya harus diserahkan kepada iblis. Kata Kunci: kebinasaan tubuh, keselamatan roh, percabulan, moral.